The Complex Relationship Between Body Mass Index and Suicide Risk: From Epidemiology to Biological Mechanisms – A Review - Świątecka, Martyna; Kaźmierczyk, Jakub; Marciszewska, Aleksandra; Buczkowska, Ewa; Jopek, Jakub; Bryksy, Sylwia; Piechowicz, Agnieszka; Popczyk, Natalia; Przybyłowska, Agnieszka; Tymchenko, Hanna (Quality in Sport, 2026)
Introduction. Suicide is one of the most serious public health problems worldwide. In the context of risk marker searches, researchers focus on Body Mass Index (BMI). Scientific studies remain unclear, indicating both a potential protective effect of obesity and an increased risk of suicidal behaviors in extreme weight categories. Purpose. This study reviews literature regarding the correlation between BMI and the risk of suicidal ideation and behaviors, considering potential underlying mechanisms. Materials and methods. A PubMed search was conducted. Epidemiological and clinical studies covering adult and adolescent populations from Europe, North America, and Asia were analyzed. The review included completed suicides, attempts, ideation, biomarkers (serotonin, leptin, cytokines), and psychosocial factors. Summary. The literature indicates a complex relationship between BMI and suicide risk, often assuming a "U" or "J" shape. Some studies found lower suicide mortality in overweight and obese individuals. However, recent research shows that extreme obesity or being underweight increases risk. Insulin resistance might lower impulsivity, but chronic inflammation and leptin resistance could increase vulnerability. For adolescents, subjective weight perception is a key risk factor. In adults, obesity can affect the selection of less lethal suicide methods. Conclusions. BMI is an important but complex marker of suicide risk. The "obesity paradox" may result from physical barriers hindering suicide completion. Clinical assessment should include body weight and its dynamic changes, subjective body image, and metabolic profile.